Prophetic conflicts in the Deuteronomistic history - Kim, Daewook (Beiträge zur Wissenschaft vom Alten und Neuen Testament, 2021)
Coversheet -- Frontpage -- Imprint -- Contents -- Acknowledgements -- Abbreviations -- 1. Introduction -- 1.1 Aims of the Study -- 1.2 Texts -- 1.3 The Deuteronomistic History4 -- 1.4 Monotheism and Syncretism -- 1.5 Methods for the Study -- 1.5.1 Rhetorical Historiography -- 1.5.2 Bakhtinian Dialogism and Fortschreibung -- 1.5.3 The Relationship between Texts -- 1.5.4 Extra-Biblical Texts and Archaeological Data -- 1.6 A Review of Previous Study -- 2. Saul, the Dead Samuel, and the Woman (1 Samuel 28:3-25) -- 2.1 Literary Analysis -- 2.1.1 The Structure of the Narrative -- 2.1.2 Implied Condemnations of Saul -- 2.1.3 Samuel and the Woman -- 2.1.4 David, the True King -- 2.2 Date -- 2.3 Religious Setting and Rhetorical Purposes -- 2.3.1 Segregation -- 2.3.2 The Rejection of Necromancy and the Redefinition of אלהים -- 2.3.3 The Diminishment of Prophecy -- 2.3.4 Emphasis on Davidic Succession and Hopes -- 2.4 Summary -- 3. The Old Prophet's Deceit, Jeroboam's Golden Calves, and the Disobedience of the Man of God (1 Kings 12:25-13:34) -- 3.1 Literary Analysis -- 3.1.1 Who is the True Prophet? -- 3.1.2 Jeroboam and the Old Prophet -- 3.1.3 YHWH's Prohibitions -- 3.2 Date -- 3.3 Religious Setting and Rhetorical Purposes -- 3.3.1 The Origin of the Golden Calves -- 3.3.2 Opposition to Syncretism -- 3.3.3 Rejection of Poly-Yahwism -- 3.3.4 From Images to the Word -- 3.4 Summary -- 4. YHWH, Baal, and Asherah (1 Kings 18:16-40) -- 4.1 Literary Analysis -- 4.1.1 Confusion between YHWH and Baal -- 4.1.2 Contrasts between YHWH and Baal -- 4.1.3 True God, True Husband -- 4.1.4 Asherah, Baal's Consort -- 4.1.5 YHWH's Devouring Fire -- 4.2 Date -- 4.3 Religious Setting and Rhetorical Purposes -- 4.3.1 YHWH, Baal, and Asherah -- 4.3.1.1 YHWH and Baal -- 4.3.1.2 YHWH and Asherah -- 4.3.1.3 Baal and Asherah -- 4.3.2 YHWH, Gods, and Goddesses -- 4.4 Summary.